Propofol or propofol/ketamine for continuous intravenous anaesthesia in dogs - Vieira, Fernando A.F. [UNESP]; Loureiro Luna, Stelio Pacca [UNESP]; Cassu, Renata Navarro (My University, 2013)
This study aimed to investigate the cardiopulmonary and analgesic effects of the continuous intravenous anaesthesia in dogs premedicated with methotrimeprazine, distributed in four groups. The anaesthesia was induced and maintained with propofol IV in groups G1 (n=6) and G1-OSH (n=8), and propofol/ketamine in groups G2 (n=6) and G2-OSH (n=8). In G1 and G2, the dogs were maintained anaesthetised during 60 minutes, while in G1-OSH and G2-OSH the dogs undergoing elective ovariohystectomy. IPPV was used immediately after induction of anaesthesia in all dogs. Electrocardiography, heart and respiratory rates, tidal and minute volume, blood pressure, rectal temperature, oximetry, capnography, arterial blood gases, plasma propofol concentration, analgesia degree, time and quality of anaesthetic recovery were evaluated. Hypothension were observed during anaesthesia. Quality of recovery was similar in all groups, but the recovery time was later in G1-OSH and G2-OSH, with dose-dependent effect. The results suggested that ketamine reduced the propofol infusion rate, however it did not modify cardiovascular depression. The infusion rates of propofol necessary to produce surgical anaesthesia were very high, leading to prolonged recovery times.
Propofol ou propofol/cetamina na anestesia por infusão contínua intravenosa em cães
Keywords: Dog; Ketamine; Ovariohysterectomy; Propofol